Effect of head-down inclined position in the treatment of upper ureteral calculi with holmium laser ureterscopic lithotripsy: a case series of 246 patients - Xiang-Yun MENG; Zi-Qing ZHU; Xin-Min ZHENG; Zhuang WU (Yixue xinzhi zazhi)
Objective To investigate the curative effect of head-down incline in holmium laser ureterscopic lithotripsy for upper ureteral calculi.Methods Clinical data was collected of patients who were diagnosed upper ureteral calculiand treated with holmium laser ureterscopic lithotripsyin head-down inclined position from April 2016 to December 2019. The effect of holmium laser ureterscopic lithotripsy in patients with upper ureteral calculi was evaluated.Results Finally 246 patients with upper ureteral calculi treated with ureteroscope holmium laser lithotripsy were included. Of them, 98 cases of intraoperative stones moved up into the renal pelvis or upper group of calyces, ureteroscope was chased to the renal pelvis or upper group of calyces, and the stones were smashed with laser. 240 patients had primary crushed stones with a success rate of 97.6%. 4 patients with upper ureteral stenosis were successfully treated with ureteroscopic holmium laser lithotripsy after indwelling the DJ tube for two weeks. In one patient, some of the stones moved upward into the medial renal calyx of the middle group, and the extracorporeal shock wave lithotripsy was successful in the later stage. One patient's stones moved up into the upper group of calyces, and the stone fragments were about 0.6 cm. Twenty-six patients with bilateral ureteral calculi were successfully treated with bilateral ureteral holmium laser lithotripsy at the same time. The operation time was 15-56 min, with an average of 26.08±11.73 min; the length of hospitalization is 4-6 days.Conclusion The head-down inclined position is safe and effective in the treatment of upper ureteral calculi byholmium laser ureterscopic lithotripsy, and the success rate of first-stage lithotripsy is high. However, we suggest performing high quality controlled studies to verify.